2017
DOI: 10.1039/c7mh00726d
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal-triggered release of singlet oxygen from an endoperoxide-containing polymeric carrier for killing cancer cells

Abstract: An endoperoxide-containing polymeric carrier was developed to realize the photothermal-triggered release of singlet oxygen for killing cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Hydrophilic polyethylene glycol was introduced in the polymer to improve the water solubility and EPR effect. The monomer DMN-acryl has been synthesized according to the previous work [26]. The monomer B1 was synthesized in four steps (See in the Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrophilic polyethylene glycol was introduced in the polymer to improve the water solubility and EPR effect. The monomer DMN-acryl has been synthesized according to the previous work [26]. The monomer B1 was synthesized in four steps (See in the Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in Figure 2(e), the absorption spectra of P1 dots displayed a strong absorption at 243 nm and a weak absorption at 689 nm, which were consistent with the absorption of DMN and B1 monomer, respectively. After capture of 1 O 2 , the destruction of conjugated structure of DMN leaded to a sharp decrease at 243 nm in the UV-Vis absorption spectra [26]. In addition, P1 dots and P1-SO dots showed almost the same emission maxima at 730 nm (Figure 2(f)), which was attributed to the luminescence of B1 (see in the Supplementary Material) and negligibly affected by the 1 O 2 loading.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phototherapy agent PPAIB and its precursor P1 were synthesized easily via radical polymerization (Scheme S1, Supporting Information) . They have been fully characterized through nuclear magnetic resonance (NMR) spectra, gel permeation chromatography (GPC), UV–vis absorption spectra, and emission spectra.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24] It was reported that methylnaphthalenes and anthracenes can be used for cancer cell damage. 12,25 However, the short lifetime made them unable to perform well in cancer treatment. 26 Although some photothermal materials have been used for accelerating ROS release, excessive temperature can also induce damage to normal tissues.…”
Section: Introductionmentioning
confidence: 99%